Spectral composition of shortwave radiation reflected and deep penetrating into snow near the Barentsburg settlement (Svalbard) - P. N. Svyashchennikov; A. V. Urazgildeeva; Y. N. Kurochkin; B. V. Ivanov; K. V. Chistyakov; D. Divin; S. Hudson (Лëд и снег, 2015)
Data on spectral composition of shortwave radiation that is reflected from snow and penetrates deep into the snow cover obtained near the Barentsburg settlement (Svalbard) are discussed in the paper. Measurements were made by the use of the spectral radiometer TriOS Ramses within the wavelength range of 280–950 nm. The results will allow more proper taking account of the anthropogenic pollution effects on the radiative properties of snow cover under conditions of industrial activity related to the coal extraction and burning in Barentsburg.